2011
DOI: 10.4314/pamj.v8i1.71078
|View full text |Cite
|
Sign up to set email alerts
|

Le mal de Pott: à propos de 82 cas

Abstract: Nous rapportant dans cette étude, les résultats de l'expérience du service de neurochirurgie du CHU Hassan II de Fès dans la prise en charge du mal de pott dans la région de Fès. Il s'agit d'une étude rétrospective de quatre-vingt-deux cas; étalée sur une période de cinq ans (janvier 2002 au décembre 2006). L'objectif de ce travail était d'illustrer les différents aspects épidémiologiques, diagnostiques et thérapeutiques de la localisation vertébrale de la tuberculose dans notre pratique. L'âge moyen de nos pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 7 publications
5
9
0
5
Order By: Relevance
“…Although skeletal TB occurs mostly in the spine, followed by the hip, knees, and foot, or ankle, the epidemiology of extrapulmonary TB and in particular musculoskeletal TB remains largely unknown in areas of high prevalence of TB [4]. The average age of our patients at the time of diagnosis was 47.5 years, which was similar to other studies conducted in Africa that reported age of adult patients with musculoskeletal TB ranging from 40 to 60 years [7, 911]. A slight male predominance of the disease has often been reported in the literature [8, 12].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Although skeletal TB occurs mostly in the spine, followed by the hip, knees, and foot, or ankle, the epidemiology of extrapulmonary TB and in particular musculoskeletal TB remains largely unknown in areas of high prevalence of TB [4]. The average age of our patients at the time of diagnosis was 47.5 years, which was similar to other studies conducted in Africa that reported age of adult patients with musculoskeletal TB ranging from 40 to 60 years [7, 911]. A slight male predominance of the disease has often been reported in the literature [8, 12].…”
Section: Discussionsupporting
confidence: 74%
“…As noted by other authors, patients with spinal TB were of lower social class [8, 13], and many of them did not present earlier with signs of pulmonary TB [10]. Several risk factors have been reported, including diabetes, nephropathy, and recent spine surgery [7]. In our study, some patients had diabetes, rheumatoid arthritis, or gout.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations